DETECTION OF OPEN BITE IN CHILDREN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The city of Samarkand has lately instituted a variety of initiatives to improve the diagnosis, treatment, and prevention of vertical deformities, particularly exposed bites. At now, many scientists and practitioners are doing extensive research into the mechanisms that lead to the emergence of this anomaly. Endogenous and exogenous factors, together with the patient's living conditions and age, are very important in therapeutic therapy. We executed preventative measures for 37 patients aged 6 to 15 with an open bite. [1,2]